Assessment of knowledge and awareness among radiology personnel regarding current computed tomography technology and radiation dose. (March 2016) - Karim, M K A; Hashim, S; Bradley, D A; Bahruddin, N A; Ang, W C; Salehhon, N
Abstract: In this paper, we evaluate the level of knowledge and awareness among 120 radiology personnel working in 7 public hospitals in Johor, Malaysia, concerning Computed Tomography (CT) technology and radiation doses based on a set of questionnaires. Subjects were divided into two groups (Medical profession (Med, n=32) and Allied health profession (AH, n=88). The questionnaires are addressed: (1) demographic data (2) relative radiation dose and (3) knowledge of current CT technology. One-third of respondents from both groups were able to estimate relative radiation dose for routine CT examinations. 68% of the allied health profession personnel knew of the Malaysia regulations entitled 'Basic Safety Standard (BSS) 2010', although notably 80% of them had previously attended a radiation protection course. No significant difference (p < 0.05) in mean scores of CT technology knowledge detected between the two groups, with the medical professions producing a mean score of (26.7 ± 2.7) and the allied health professions a mean score of (25.2 ± 4.3). This study points to considerable variation among the respondents concerning their understanding of knowledge and awareness of risks of radiation and CT optimization techniques.